Florence and the history of glasses: between fake news and technological progress - Baldanzi, Elisabetta; Farini, Alessandro (Il Colle di Galileo, 2024)
Glasses are definitely one of the most important applications of optics. Yet, although lenses had already existed for a long time, it was not until the late 13th century that they were used to improve human vision. Vasco Ronchi, founder of the Italian National Institute of Optics, explains this delay by, among other things, a lack of knowledge of the theory of optics and a distrust of what was seen through instruments that could interfere with reality. What Ronchi is convinced of is that lenses were born in a ‘modest, uncultivated environment, against the advice of science’ and even their name (lenses, derived from the lentils they were shaped like) testifies to their popular origin.